1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Expectation Value

  1. Jun 27, 2009 #1
    1. The problem statement, all variables and given/known data
    Find the expectation value <x> if:
    from 0 <= x <= a, psi = A x/a
    from a <= x <= b, psi = A(b-x)/(b-a)

    Normalizing gives me that A = sqrt(3/b) (verified correct)

    2. Relevant equations

    3. The attempt at a solution
    [tex]<x> = \int_0^b x \psi^2 dx = \int_0^a \frac{A^2 x^3}{a^2}dx + \int_a^b A^2 \frac{x (b-x)^2 }{(b-a)^2} dx[/tex]

    [tex]\int_0^a A^2 \frac{ x^3 }{ a^2} = A^2 \frac{ a^2 }{4} = 3/4 a^2/b[/tex]

    [tex]A^2 \int_a^b \frac{x(b-x)^2}{(b-a)^2} dx = -A^2 \frac{x (b-x)^3}{(b-a)^2} - A^2 \frac{(b-x)^4}{12(b-a)^2}[/tex] eval from b to a

    [tex]<x> = \frac{3a^2}{4b } + \frac{+ 3(b-a)a}{b} + \frac{3(b-a)^2}{12b} = \frac{-8a^2 + b^2 + 10ab}{4b}[/tex]

    The answer is supposed to be (2a+b)/4... Does anyone see where I've gone wrong? I have double checked the antideriv. for the x(b-x)^2 integral and it seems to work.
    Last edited: Jun 27, 2009
  2. jcsd
  3. Jun 27, 2009 #2


    User Avatar
    Science Advisor
    Homework Helper

    The antiderivative of the x(b-x)^2 does NOT work. Try it again. How did you get that form anyway?
  4. Jun 27, 2009 #3
    Thanks for your reply

    I used integration by parts,

    u = x
    du = dx

    dv = (b-x)^2
    v = -(b-x)^3/3

    vu - int(v du)

    [tex]\frac{-(b-x)^3 x}{3} - \frac{(b-x)^4}{12}[/tex]

    [tex]A^2 \int_a^b \frac{x(b-x)^2}{(b-a)^2} dx = \frac{A^2}{(b-a)^2} * (\frac{-x(b-x)^3}{4} - \frac{(b-x)^4}{12})[/tex]
    I ran through it again but I can't seem to see what I am doing incorrectly.
    Last edited: Jun 27, 2009
  5. Jun 27, 2009 #4
    The 0 to a integration seems to be correct.

    The a to b integration seems little bit weird. The approach that you did by using the integration by part can lead you to the answer.

    [tex]A^2 \int_a^b \frac{x(b-x)^2}{(b-a)^2} dx = \frac{A^2}{(b-a)^2} * (\frac{-x(b-x)^3}{3} - \frac{(b-x)^4}{12})[/tex]

    [tex] = \frac{3}{b} (\frac{a(b-a)}{3}+\frac{(b-a)^2}{12})[/tex]

    Now you can get <x> value by doing:


    Pretty much a straight forward process.

    Hope it helped =)
  6. Jun 27, 2009 #5


    User Avatar
    Science Advisor
    Homework Helper

    In the original post you were missing the denominator 3 on the (b-x)^3 part. In post 3 you had it except in the last line you replaced it with a 4. You are doing everything right. I think you are just making a bookkeeping error. You could also integrate x*(b-x)^2 by just expanding it into xb^2-2bx^2-x^3. That's what I did.
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook